The Quality of Library Communication Services in the Library Department of South Sulawesi Province - Saputra, Efan; Saleh, Noerjihad; Santalia, Indo (Jurnal Mercusuar, 2022)
This study discusses the professionalism of librarians in improving the quality of communication services in the Library and Archives Office of South Sulawesi Province. The purpose of this research is to determine the professionalism of librarians, the quality of services, and efforts to improve the quality of services in the Library and Archives Office of South Sulawesi Province. This research uses a qualitative research method, data collection is done through observation, interviews, and documentation. Data analysis techniques are done through observation, data reduction, data presentation, and data verification. Data validity testing is done using time triangulation, which is carried out by checking observations and interviews at different times. The results of the study show that 1) Librarians in the Library and Archives Office of South Sulawesi Province are dominated by librarians who have a background in Library Science education and the professionalism of librarians has been shown by their ability to perform tasks and work according to Standard Operating Procedures (SOP), provide a friendly attitude to every visitor who enters the library, direct visitors in finding the required collection and guide them in using the facilities available. 2) The service provided by librarians is not yet of good quality due to the lack of education on the use of OPAC for visitors and some librarians are not friendly in providing services. 3) Efforts to improve the quality of services are continuously carried out by the Library and Archives Office of South Sulawesi Province by conducting various activities such as Roadshows, Technical Guidance on Excellent Services, Personality Training, and training related to library services.